In Defence of a Manic Defence: A Therapist’s Experience of Humour in Psychotherapy - Ciurlionis, Craig (Auckland University of Technology, 2021)
The following is a heuristic study: a first-person exploration of humour, using my own experience to illuminate this particularly fascinating aspect of humanity, and an infrequently discussed, yet potentially impactful, aspect of the therapeutic endeavour. I also engage with psychotherapeutic literature and aspects of popular culture to attempt to determine important themes. These include the fact that humour is often considered inappropriate, despite having very few vocal proponents, is frequently a response to power, and can act as a boost to one’s sense of resilience. I look at the potential benefits and pitfalls of humour in therapy and attempt to illustrate that although it is often overlooked, humour has the potential to be an enjoyable, connecting experience.
Keywords: Humour; Psychotherapy; New Zealand; Manic defence